Real-time assessment of the Ganga river during pandemic COVID-19 and predictive data modeling by machine learning - Singh, J.; Swaroop, S.; Sharma, P.; Mishra, V. (Institute for Ionics, 2023)
In this study, four water quality parameters were reviewed at 14 stations of river Ganga in pre-, during and post-lockdown and these parameters were modeled by using different machine learning algorithms. Various mathematical models were used for the computation of water quality parameters in pre-, during and post- lockdown period by using Central Pollution Control Board real-time data. Lockdown resulted in the reduction of Biochemical Oxygen Demand ranging from 55 to 92% with increased concentration of dissolved oxygen at few stations. pH was in range of 6.5–8.5 of during lockdown. Total coliform count declined during lockdown period at some stations. The modeling of oxygen saturation deficit showed supremacy of Thomas Mueller model (R2 = 0.75) during lockdown over Streeter Phelps (R2 = 0.57). Polynomial regression and Newton’s Divided Difference model predicted possible values of water quality parameters till 30th June, 2020 and 07th August, 2020, respectively. It was found that predicted and real values were close to each other. Genetic algorithm was used to optimize hyperparameters of algorithms like Support Vector Regression and Radical Basis Function Neural Network, which were then employed for prediction of all examined water quality metrics. Computed values from ANN model were found close to the experimental ones (R2 = 1). Support Vector Regression-Genetic Algorithm Hybrid proved to be very effective for accurate prediction of pH, Biochemical Oxygen Demand, Dissolved Oxygen and Total coliform count during lockdown.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Artificial neural network; Biochemical oxygen demand; Dissolved oxygen; Modeling; pH; The Ganga; Total Coliform Count; Ganges River; Biochemical oxygen demand; Dissolution